PERSUASIVE ASSISTANCE AND PROBLEM-SOLVING FOR THE ESTABLISHMENT OF VILLAGE-OWNED ENTERPRISES - Suyanto Dr (SYNTIFIC, 2023)
Background. Programs from local governments to develop and prosper village communities through Village-Owned Enterprises (hereinafter better known as BUMDes) are in line with Law No. 6/2014 article 1 paragraph 6. However, the establishment of BUMDes is still unknown to the village community and many problems make village communities unable to take advantage of BUMDes. The purpose of this activity was to 1) increase knowledge of Tanjung village communities about BUMDes, 2) determine village potential, establishment, and management of BUMDes. Implementation Method. This community service activity was in collaboration with the Lamongan Government Sector and Indonesian Notary Association of East Java Regional Management through